Nursing students' perception of medical errors: A cross‐sectional study in a university - Victoria Bam; Adwoa Safowaa; Alberta Yemotsoo Lomotey; Abena Safoa Nkansah (Wiley, 2021)
Abstract Aim To assess the perception of nursing students on medical errors. Design A descriptive cross‐sectional survey. Method Data were collected from March-April 2019 in a university in Ghana from two hundred (200) students using simple random sampling and analysed with SPSS version 21. Results Mean age of respondents was 22.64 years. Medication error was perceived as the most common medical errors (MEs; 76%). Negligence was perceived as the most common cause of MEs (80.5%); nurses and doctors (84.5%-89.5%) were considered as staff who make most MEs. Respondents perceived that students commit MEs due to less knowledge about procedures (79%) and inadequate supervision (77%) in the clinical setting. Conclusion Medication errors were observed as the most common of MEs that can affect patients' safety. Taking prudent measures in addressing this can reduce MEs in health facilities. Enhanced supervision and effective ways of teaching drug administration are recommended.